Gambaran upaya pencegahan penyakit skabies terhadap pengetahuan dan sikap siswa - Rahmatulla, Ahmat Ali; Subandi, Andi; Rudini, Dini; Sari, Lisa Anita; Mawarti, Indah (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Scabies is a contagious skin infestation often found in densely populated environments such as Islamic boarding schools. Close physical contact between students and limited personal hygiene practices can increase the risk of transmission. Improving knowledge and attitudes regarding scabies prevention is crucial to suppress the spread of this disease. Purpose: To describe the level of students' knowledge and attitudes regarding scabies prevention. Method: This study used a quantitative descriptive design using a cross-sectional approach. Ninety-nine students participated. Data were collected using a structured questionnaire that assessed knowledge and attitudes regarding scabies prevention. Data were analyzed univariately and presented as frequency distributions and percentages. Results: The majority of students (48.5%) had sufficient knowledge about scabies prevention, 32 (32.3%) had poor knowledge, and 19 (19.2%) had good knowledge. Furthermore, the attitude variable showed that the majority of students (62.6%) were in the fair attitude category, while 37 (37.4%) were in the very good attitude category, and no students had poor attitudes. Conclusion: Students' knowledge and attitudes toward scabies prevention were generally in the fair category, but still need improvement, especially in the group with poor knowledge.   Keywords: Attitude; Knowledge; Scabies; Students.   Pendahuluan: Skabies merupakan infestasi kulit menular yang sering ditemukan pada lingkungan padat hunian seperti pondok pesantren. Kontak fisik yang erat antar siswa serta keterbatasan praktik kebersihan diri dapat meningkatkan risiko penularan. Peningkatan pengetahuan dan sikap terhadap pencegahan skabies menjadi hal penting untuk menekan penyebaran penyakit ini. Tujuan: Untuk menggambarkan tingkat pengetahuan dan sikap siswa mengenai pencegahan skabies. Metode: Penelitian dengan desain deskriptif kuantitatif menggunakan pendekatan cross-sectional. Responden berjumlah 99 siswa. Pengumpulan data dilakukan menggunakan kuesioner terstruktur yang menilai pengetahuan dan sikap terkait pencegahan skabies. Data dianalisis secara univariat dan disajikan dalam bentuk distribusi frekuensi serta persentase. Hasil: Mayoritas siswa memiliki pengetahuan kategori cukup tentang pencegahan skabies sebanyak 48 orang (48.5%), pengetahuan kurang 32 orang (32.3%), dan pengetahuan baik 19 orang (19.2%). Selain itu, variabel sikap menunjukkan sebagian besar siswa berada pada kategori sikap cukup sebanyak 62 orang (62.6%), sedangkan sikap sangat baik sebanyak 37 orang (37.4%), dan tidak ada siswa dengan sikap kurang. Simpulan: Pengetahuan dan sikap siswa terhadap pencegahan skabies secara umum berada pada kategori cukup, tetapi masih perlu ditingkatkan terutama pada kelompok dengan pengetahuan kurang.   Kata Kunci: Pengetahuan; Siswa; Sikap; Scabies.